Molecular Mechanisms Regulating Macrophage Response to Hypoxia - Rahat, Michal A.; Bitterman, Haim; Lahat, Nitza (Frontiers in Immunology, 2011)
Monocytes and Macrophages (Mo/Mϕ) exhibit great plasticity, as they can shift between different modes of activation and, driven by their immediate microenvironment, perform divergent functions. These include, among others, patrolling their surroundings and maintaining homeostasis (resident Mo/Mϕ), combating invading pathogens and tumor cells (classically activated or M1 Mo/Mϕ), orchestrating wound healing (alternatively activated or M2 Mo/Mϕ), and restoring homeostasis after an inflammatory response (resolution Mϕ). Hypoxia is an important factor in the Mϕ microenvironment, is prevalent in many physiological and pathological conditions, and is interdependent with the inflammatory response. Although Mo/Mϕ have been studied in hypoxia, the mechanisms by which hypoxia influences the different modes of their activation, and how it regulates the shift between them, remain unclear. Here we review the current knowledge about the molecular mechanisms that mediate this hypoxic regulation of Mϕ activation. Much is known about the hypoxic transcriptional regulatory network, which includes the master regulators HIF-1 and NF-κB, as well as other transcription factors (e.g. AP-1, Erg-1), but we also highlight the role of post-transcriptional and post-translational mechanisms. These mechanisms mediate hypoxic induction of Mϕ pro-angiogenic mediators, suppress M1 Mϕ by post-transcriptionally inhibiting pro-inflammatory mediators, and help shift the classically activated Mϕ into an activation state which approximate the alternatively activated or resolution Mϕ.